ANALISIS SEMIOTIKA ROLAND BARTHES TERHADAP NILAI NASIONALISME DALAM NOVEL TITIK NADIR KARYA WINDY JOANA - Chairun Nisa; Roita Sinaga (FKIP, Universitas Palangka Raya, 2023)
The value of nationalism can be contained in a literary work because it is part of the social reality in society. This study aims to determine the forms of meaning based on the semiotic lexis according to Roland Barthes. This study used a qualitative approach with data collection techniques, observing and noting. Through the character Nadir in the novel Titik Nadir, the true life of students is revealed, not only academic problems but the influence of the students themselves in the life of the nation. The analysis carried out by researchers using Roland Barthes' semiotic theory in the novel Titik Nadir includes; (1) hermeneutic code, (2) semic code (connotative code); (3) symbolic code (4) preoretic code (action code), (5) gnomic (cultural) code. The value of nationalism in this novel is repeatedly represented in student activities such as demonstrations and the important incident, Anger Makassar.